김치공장 부산물 혼합처리에 따른 우분의 퇴비화특성 및 시비효과 - 김영선; Young-sun Kim; 조성현; Sung-hyun Cho; 이태순; Tae-soon Lee; 정제용; Je-yong Jeong; 안지예; Ji-ye An; 송혜연; Hye-yeon Song; et al. (유기물자원화, 2017)
본 연구는 수분조절제로서 김치공장 부산물(KFW) 처리에 따른 우분의 퇴비화 특성 및 퇴비의 시비에 따른 상추의 생육에 미치는 영향을 조사하기 위해 수행되었다. 실험에 사용된 퇴비 처리구는 대조구(우분65 %+톱밥35 %), KFW 5 % 처리구(우분 65 %+톱밥30 %+KFW 5 %), KFW 10 % 처리구(우분 65 %+톱밥25%+KFW 10 %) 및 KFW 15 % 처리구(우분 65 %+톱밥20 %+KFW 15 %)로 설정하였다. 퇴비화 25일 경과 후부터 KFW 처리구의 온도는 대조구보다 낮았다. 대조구와 비교할 때, KFW 15 % 처리구의 수분함량은 약 5℃ 정도 낮았고, 유기물함량과 질소함량은 약간 높았으며, pH와 유기물대 질소비는 대조구와 비슷하였다. 발아지수를 통한 부숙도 평가에서 KFW 처리구들은 퇴비화 후 25일경에, 대조구는 35일경에 70이상을 나타내어 부숙이 완료되었다. KFW를 처리한 우분퇴비를 시비하였을 경우 KFW 10 % 처리구와 KFW 15 % 처리구에서 상추의 건물중이 각각 84 %와 67 %씩 증가하였다. 이러한 결과를 종합할 때, 김치공장 부산물은 가축분 퇴비화 과정에서 퇴비원료 및 수분조절제로서 사용이 가능하다는 것을 알 수 있었다. This study was conducted to evaluate effects of Kimchi factory waste (KFW) as bulking agent on physicochemical properties of cow manure (CM) composting and of its application on lettuce growth. Treatments were designed as follows; CM compost [65 % CM + 35 % sawdust (SD); control], KFW 5 % (65 % CM + 30 % SD + 5 % KFW), KFW 10 % (65 % CM + 25 % SD + 10 % KFW) and KFW 15 % (65 % CM + 20 % SD + 15 % KFW). After composting for 25 days, temperature of KFW treatments was lower than that of control. As compared with control, water content of KFW 15 % treatment was low about 5℃, and content of organic matter (O.M.) and nitrogen (N) was higher. pH and O.M./N ratio of KFW treatments or control were unaffected. In comparison with germination index (G.I.), G.I.s of KFW treatments were more than 70 on 25 days and G.I. of control on 35 days. As applied with KFW composts in lettuce, dry weight of KFW 10 % and KFW 15 % were increased by 84 % and 67 %, respectively, than that of control. These results indicated that Kimchi factory waste was possible to use as the compost law materials in livestock manure composting and to replace some sawdust as bulking agent.